Variational principles in quantum statistical mechanics - Providência, João da (1987)
The principle of least information is used to derive the inequality between the arithmetic and the geometric mean. Some important variational results in quantum statistical mechanics (Peierls and Bogolyubov inequalities) are pedagogically reviewed. Emphasis is put on the distinction between mixed states describing metastable and stable equilibrium.